The activity of human metadata creation and the semantic web. (1st January 2015) - Enoksson, Fredrik; Bälter, Olle
This paper presents an explorative study of the human activity of creating metadata, done with the purpose of exploring the practices of this activity and how those can potentially impact the utility of the metadata as it is exposed on a level that enables semantic collaboration, like the semantic web. Previous research around human metadata creation seems to indicate that how the activity is carried out has a common core, but is unique in each situation on how it can be improved. The data for this study was gathered through interviews and analysed using activity theory. The analysis of the data gathered through the interviews indicates that the main objective of the activity is to enable discovery within a collection. Metadata is however created with a community of users in mind, which is sometimes reflected in metadata creation guidelines. These guidelines can in turn impact the discoverability across these communities as metadata is exposed on the semantic web.